Vitiligo Appearing after Oral Isotretinoin Therapy for Acne - Amal A. Kokandi (Hindawi Limited, 2018)
Isotretinoin is an effective treatment for severe and scarring acne. In this report, we describe a case developing vitiligo after isotretinoin therapy for scarring acne. It is not known whether this was a coincidence or might be precipitated by the treatment.